International Night - a night of culture sharing of various countries - Mohammad Hakimi, Kamarudin (2018)
Some 900 international students from 30 countries were involved in the International Night event organised by Universiti Malaysia Pahang (UMP) International Office held at Block W, UMP Gambang Campus on December 19, 2018.